Sentimental Analysis of online study of College and School going Students - Tiwari, Mamta; Dutta, Swagata (International Journal of Computer Sciences and Engineering, 2021)
Online research opinion mining and sentiment analysis of college and school going students may accurately represent the students learning circumstances, providing the theoretical foundation for further revisions of teaching programmes. Analysis of student learning experiences using data mining and sentiment analysis in online learning community may lay the theoretical groundwork for future changes to teaching programmes. The term "online study" is the study that takes place using the internet. One of the objectives of the project is the creation and assessment of a conceptual model that incorporates students' learning and teaching preferences as well as technological experience, as well as their feelings about how these things impact their learning and teaching. An online survey of college and school going students was performed. It was found that some clusters of students were formed after applying k-means clustering machine learning algorithm which shows us that some changes should be adopted in the current online study scenario. Prediction and visualization of the data is done by seaborn, matplotlib python libraries which helps us to understand the pattern of the data. It is expected that this assessment would create a better system for students to study. Discoveries corroborate hypotheses about the influence of sentiment on factors such as attitude, favorite hobbies, and technological experience.